Correlation Self-Efficacy and Adversity Quotient of Students at SMK Muhammadiyah 2 Wedi Klaten - Luthfi Ismawati; Isnanita Noviya Andriyani (research, training and philanthropy institution Natural Aceh, 2022)
This study aims to determine whether there is a correlation between self-efficacy and adversity quotient for students of SMK Muhammadiyah 2 Wedi Klaten. This type of research uses quantitative research methods with a correlational approach. Sampling methods using simple random sampling with data collection techniques in the form of a scale. The research subjects were 70 students from class XI of SMK Muhammadiyah 2 Wedi, Klaten. The results obtained correlation analysis (rxy) of 0.708 with a p-value 0.000 that is lower than 0.05, meaning that there is a significant positive correlation between self-efficacy and the student's adversity quotient. This can indicate that the higher the student's self-efficacy, higher the adversity quotient of the student, then Ho is rejected and Ha is accepted. Self efficacy and adversity quotient in students of SMK Muhammadiyah 2 Wedi, Klaten are classified as moderate. The coefficient of determination (R2) of the correlation is 0.724, meaning that self-efficacy contributes effectively to the adversity quotient by 72%, which means there are 28% of the other factors that affect students adversity quotient